El léxico latino de la fisiología en los textos del humanismo médico valenciano: la tradición de spiritus - Santamaría Hernández, María Teresa (Myrtia: Revista de filología clásica, 1999)
The analysis of the tradition of some concrete medical words (spiritus , pneuma , flatus ) and their corresponding concepts serves us to characterize the language of the humanist Valencians doctors in the XVI century: when building up the Latin language of classical levels, it may turn ont to be significative the election of terms as well as the philologist interests, that are lacking of medieval medical texts, which lead to it. The preferences of vocabulary become at the same time, in a good instrument of comparison and relationship between the humanist doctors of our country and the European medical humanism.